Stock Return of Companies on the Indonesia Stock Exchange: A Comparative Study Before and After a Stock Split - Senja Rosmaida Maretha Manik; Dimas Sumitra Danisworo; Ade Ali Nurdin; Benny Barnas (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
A stock split is one of the corporate actions that the company can take to reduce the nominal value of the share price. A stock split is done by increasing the number of outstanding shares to encourage more share trading. This study aims to test whether there is a significant change in the performance of stock returns before and after the stock split operation. This study will use a quantitative research methodology, and the sampling strategy will be purposive sampling. These two things will go hand in hand. The data type used is secondary data, which is the daily closing price of shares. These prices are then processed so that the stock returns can be calculated. The length of time for the study was 20 days, starting ten days before the stock split activity and ending ten days after the stock split activity. This is done according to the stock split date. Because the normality test results showed that the returns obtained before and after the stock split are not normally distributed, the Wilcoxon marked rating test applied in SPSS version 25 will be used to test the hypothesis regarding the distribution of returns before and after the stock split. Hypothesis testing resulted in the conclusion that there is a substantial difference between return and stock split. This conclusion was reached based on the test findings.